Folklore in the modern world - Dorson, Richard M. (Richard Mercer), 1916-1981.; International Congress of Anthropological and Ethnological Sciences 1973 : Chicago, Ill.) (The Hague : Mouton, 1978)
Papers presented at the 9th International Congress of Anthropological and Ethnological Sciences, Chicago, 1973.
Papers prepared for the 9th International Congress of Anthropological and Ethnological Sciences, Chicago, 1973.
Includes bibliographies and index.
Keywords: Folklore -- Congresses